Anmeldelser - Topp, Morten (Danish Yearbook of Musicology, 1979)
Review of: Per Nørgård: »Gilgamesh«. Dansk Musik Antologi 025-026. Björn Haugan, Helge Lannerbäck, Britt Marie Aruhn, Jørgen Hviid, Ranveig Eckhoff, Merete Bækkelund, Birger Eriksson, Solwig Grippe, Annika Bartler, Rolf Leanderson, Monika Hagelin, Eva Larsson, Erik Backman, Dieter Schlee, Karl-Robert Lindgren, Richard Berg, Carina Morling, Margit Teimar, Margaretha Ljunggren, Ulla Broström-Sköld, Karin Öquist, Ingrid Ståine , medlemmer af Sveriges Radios Symfoniorkester, Támàs Vetö. EMI6C 063-39190-191.